Use of productive methods in the Didactic discipline of Chemistry for the Bachelor of Education. Chemistry (REDEL. Revista Granmense de Desarrollo Local, 2021)
The Didactics of Chemistry at the different levels of education in Cuba implements the general positions of didactics in the teaching-learning process of chemistry, in correspondence with the objectives and content of planned learning. Taking into account the development and knowledge achieved, the goals to be achieved by the students are in turn a starting point for the different Chemistry teaching methodologies that can be developed derived from the theoretical positions that make up this didactics. The objective of this research is to design a proposal for the didactic-methodological structuring of a conference, with the use of productive methods in the Chemistry Didactics discipline for students in the 3rd year of the Bachelor of Education career. Chemistry at the University of Granma. The development is based on the use of theoretical methods, such as analytical-synthetic and inductive-deductive; methods of the empirical level, including observation and survey. The current and novelty of the research lies in the dynamic nature of the different planned activities and at the same time its developer nature, which contribute to the learning of the Chemistry subject in an active and conscious way.
Keywords: teaching – learning; productive methods; didactic-methodological structuring; Chemistry Didactics